Teacher Problems in Implementing a Web-Based Assessment System in Referral Schools in West Sumatra - Dian Fauziah; Warsono Warsono; Muhammad Jacky (JED (Jurnal Etika Demokrasi), 2022)
Technological developments certainly affect various areas of life. Among these aspects of education can not be separated from the development and progress of technology. One of the advances applied to the education system is the change in the assessment system carried out by teachers in schools, from manual switching to web and IT-based. In this change, there are several problems and constraints that need to be adjusted. The purpose of this study was to find out the problems of teachers in implementing web-based assessments and the teacher's steps in dealing with the problems of web-based assessment in West Sumatra reference high schools. This study was analyzed using the structural functional theory proposed by Talcott Parsons known as the AGIL scheme. This study used a qualitative approach with an intrinsic case study type. The selection of informants was done by purposive sampling with the number of informants 65 people. The data was collected by means of active participation, observation, in-depth interviews and documentation study. To obtain the validity of the data, triangulation was carried out, namely, triangulation of sources and triangulation of techniques. The data obtained were analyzed using the Miles and Huberman analysis model (data reduction, data presentation, and conclusion). The findings of this study are: (1) the obstacles faced by teachers, such as: teachers experience difficulties when inputting grades, it takes a long time, problems with the e-report, system and internet network, lack of student motivation to learn and compete, loss of teacher enthusiasm for teaching; (2) the school's strategies as a form of adaptation to the implementation of E-report cards are: ranked score raport, intervention from the school, the school's target is to graduate students to state universities. The results of this study are useful as input for schools that have used the e-report card assessment system, so that the assessment can be carried out properly and can be accounted for.Perkembangan teknologi tentunya mempengaruhi berbagai bidang kehidupan. Di antaranya pada aspek pendidikan juga tidak lepas dari perkembangan dan kemajuan teknologi. Salah satu kemajuan yang diterapkan pada sistem pendidikan adalah perubahan sistem penilaian yang dilakukan oleh guru di sekolah, dari penilaian manual menjadi berbasis web dan berbasis IT. Adanya perubahan ini, muncul beberapa masalah dan kendala yang perlu disesuaikan. Tujuan dari penelitian ini untuk mengetahui problematika guru dalam melaksanakan penilaian berbasis web dan langkah guru dalam menyiasati problematika penilaian berbasis web  di SMA rujukan Sumatera Barat. Penelitian ini dianalisis dengan menggunakan teori struktural fungsional yang dikemukakan oleh Talcott Parsons yang dikenal dengan skema AGIL. Penelitian ini menggunakan pendekatan kualitatif dengan tipe penelitian studi kasus intrinsik. Pemilihan informan dilakukan secara purposive sampling dengan jumlah informan 65 orang. Pengumpulan data dilakukan dengan cara observasi partisipasi aktif, wawancara mendalam dan studi dokumentasi. Untuk mendapatkan keabsahan data dilakukan triangulasi yaitu, triangulasi sumber dan triangulasi teknik. Data yang diperoleh dianalisis dengan menggunakan model analisis Miles dan Huberman (reduksi data, penyajian data, dan penarikan kesimpulan). Temuan penelitian ini adalah: (1) kendala yang dihadapi guru seperti: guru mengalami kesulitan saat penginputan nilai, membutuhkan waktu lama, masalah pada sistem e-rapor dan jaringan internet, kurangnya motivasi siswa untuk belajar dan berkompetisi, hilangnya semangat guru untuk mengajar; (2) strategi yang dilakukan sekolah sebagai bentuk adaptasi terhadap pelaksanaan E-rapor adalah : pengkatrolan nilai rapor, intervensi dari pihak sekolah, sasaran sekolah adalah meluluskan siswanya ke perguruan tinggi negeri. Hasil penelitian ini berguna sebagai masukkan bagi sekolah yang sudah menggunakan sistem penilaian e-rapor, agar penilaian dapat terlaksana dengan baik dan dapat dipertanggungjawabkan.